OPTIMALISASI PENDAPATAN USAHATANI MELALUI KOMBINASI PENJUALAN JAGUNG MUDA DAN JAGUNG KERING DI DESA KARANDU KECAMATAN ANGGOTOA KABUPATEN KONAWE DI BAWAH BIMBINGAN - Syarbiah, Sarty (Aksara Public, 2019)
This study aims to compare the cost and income of corn sold by farmers in the form of young corn and dry corn and the optimal combination between the sale of young corn and dry corn so that farmers' income increases in the Karandu Village, Anggotoa District, Konawe Regency. The results showed that the cost of producing young corn was Rp. 4,256,250 / Ha / MT with an income of Rp. 6,252,599, -Ha / MT while dry corn production costs Rp. 3,898,412 / Ha / MT with an income of Rp. 1,104,220 / Ha / MT this shows that the income of young corn farming is greater than dry corn and the optimal combination of the combination that produces the most income is a combination of X1 or young corn covering 2,747 ha and dry corn = 0 ha. In other words, to get maximum income which is Rp. 17,175,889 / ha, farmers must use all their land to cultivate young corn. This is due to the significant difference in income of young corn with dry corn, which is an average of Rp. 6,252,599-Rp. 1,104,220=Rp.5,148,379.